Front Vowels of English as a Foreign Language Produced by Proficient Brazilian Speakers - de Castro Lima, Crislaynne (2023)
This research aims to investigate the production of front vowels in English as a foreign language by proficient Brazilian Portuguese speakers. The methods consisted of analyzing the production of English front vowels by two groups: native and foreign (proficient Brazilian) speakers of English. An acoustic-based analysis was performed based on the acoustic parameters of the first three vowel formants, other than vowel duration. A total of eleven acoustic features were computed. For the statistical procedures, a two-way analysis of variance (ANOVA) was carried out. Results pointed out to significant differences between groups for the third formant mean, slope of the first formant, and vowel duration. It was concluded, albeit on a preliminary basis, that, even for foreign language proficient speakers, the cognitive effort imputed when producing vowels in the target language is affected by the speaker’s mother tongue in terms of labial protrusion, maintenance of mandibular excursion and intrinsic duration of vowel elements. Furthermore, it is possible to infer that the studied parameters can contribute to the teaching of foreign language pronunciation.